Case studies of brain fag syndrome in South Africa - Finnemore, Gerard le Cornu (Rhodes University, Faculty of Humanities, Department of Psychology, 2001)
Against the background of culture bound syndromes and the universalism/relativism debate, this research set out to investigate the diagnosis of brain fag syndrome by examining case studies in a South African context. Diagnostic criteria were identified by way of an analysis of the symptoms reported by a convenience sample of 20 black students experiencing problems related to study. In-depth case studies were conducted with three of the participants from the sample who most thoroughly met the criteria for brain fag syndrome. In a comparison between the brain fag diagnoses and the DSM-IV diagnoses, it was established that while the DSM-IV was not without merit in a cross cultural context, cultural differences were found which suggested the usefulness of the brain fag syndrome diagnosis. A speculative statement on the universalism/relativism debate was proposed based on the principle of complementarity derived from Quantum physics.
Keywords: Brain fag syndrome; Brain -- Diseases